2022
DOI: 10.1093/oncolo/oyac084
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Lifestyle Changes, Mammographic Breast Density, and Breast Cancer

Abstract: In screening for breast cancer (BC), mammographic breast density (MBD) is a powerful risk factor that increases breast carcinogenesis and synergistically reduces the sensitivity of mammography. It also reduces specificity of lesion identification, leading to recalls, additional testing, and delayed and later-stage diagnoses, which result in increased health care costs. These findings provide the foundation for dense breast notification laws and lead to the increase in patient and provider interest in MBD. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 77 publications
0
6
0
1
Order By: Relevance
“…The associations between parity-related factors including parity, breastfeeding, and increased density were reported in a recent study, suggesting a higher proportion of epithelial tissue related to parity and decreased density (Azam et al ., 2019). A recent meta-analysis and a review identified HRT use and increased mammographic density (Azam et al ., 2020; Lester et al ., 2022). Breast epithelial cell proliferation or stromal edema due to estrogen and progestin exposure was suggested as a possible mechanism of this association, and the increased association among estrogen plus progestin combination HRT users compared to other HRT regimens supported this mechanism (Azam et al ., 2020; Lester et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The associations between parity-related factors including parity, breastfeeding, and increased density were reported in a recent study, suggesting a higher proportion of epithelial tissue related to parity and decreased density (Azam et al ., 2019). A recent meta-analysis and a review identified HRT use and increased mammographic density (Azam et al ., 2020; Lester et al ., 2022). Breast epithelial cell proliferation or stromal edema due to estrogen and progestin exposure was suggested as a possible mechanism of this association, and the increased association among estrogen plus progestin combination HRT users compared to other HRT regimens supported this mechanism (Azam et al ., 2020; Lester et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…origines asiatiques) contribuent à la densité mammaire, des facteurs modifiables comme l'exposition aux hormones (p. ex. utilisation de la pilule contraceptive, hormonothérapie), la consommation d'alcool et l'alimentation contribuent aussi à une densité mammaire plus élevée 9 .…”
Section: La Densité Mammaire : Définitions Et Risquesunclassified
“…8 Although many nonmodifiable factors, such as genetics and race (eg, Asian heritage) contribute to breast density, modifiable factors such as hormone exposure (eg, oral contraceptive pill use, hormone replacement therapy), alcohol intake, and diet can also contribute to increased breast density. 9 The risks of dense breasts are 3-fold. First, extremely dense breasts confer a risk of breast cancer that is greater than that of having a first-degree relative with breast cancer.…”
Section: Breast Density: Definitions and Risksmentioning
confidence: 99%